Influence of Epicuticular Physicochemical Properties on Porcine Rotavirus Adsorption to 24 Leafy Green Vegetables and Tomatoes - Lu, Lu; Ku, Kang-Mo; Palma-Salgado, Sindy Paola; Storm, Andrew Page; Feng, Hao; Juvik, John A.; Nguyen, Thanh H. (PLOS ONE, 2015)
Foodborne diseases are a persistent problem in the United States and worldwide. Fresh produce, especially those used as raw foods like salad vegetables, can be contaminated, causing illness. In this study, we determined the number of rotaviruses adsorbed on produce surfaces using group A porcine rotaviruses and 24 cultivars of leafy vegetables and tomato fruits. We also characterized the physicochemical properties of each produce’s outermost surface layer, known as the epicuticle. The number of rotaviruses found on produce surfaces varied among cultivars. Three-dimensional crystalline wax structures on the epicuticular surfaces were found to significantly contribute to the inhibition of viral adsorption to the produce surfaces (p = 0.01). We found significant negative correlations between the number of rotaviruses adsorbed on the epicuticular surfaces and the concentrations of alkanes, fatty acids, and total waxes on the epicuticular surfaces. Partial least square model fitting results suggest that alkanes, ketones, fatty acids, alcohols, contact angle and surface roughness together can explain 60% of the variation in viral adsorption. The results suggest that various fresh produce surface properties need to be collectively considered for efficient sanitation treatments. Up to 10.8% of the originally applied rotaviruses were found on the produce surfaces after three washing treatments, suggesting a potential public health concern regarding rotavirus contamination.